An Exponential Curve Relationship Between Serum Urate and Migraine: A Cross-Section Study From NHANES - Hong, Peiwei; Liu, Yao; Wan, Yang; Xiong, Hai; Xu, Yanming (Frontiers in Neurology, 2022)
Background: Migraine is a common neurological disease and an important cause of disability worldwide. Serum urate is the end product of purine metabolism in Homo sapiens and other hominoids. Previous studies about the serum urate level in migraine were contradictory. Hence, we present a cross-section study to clarify the association between serum urate and migraine and explore the dose effect of serum urate on migraine. Materials and methods: The data for this cross-section study was acquired from the National Health and Nutrition Examination Survey (NHANES). A diagnosis of migraine was made through patient self-reported and prescription medication. For data analysis, the weighted linear regression model, weighted chi-square test, logistic regression models, smooth curve ﬁttings, and the two-piecewise linear regression model were utilized for data analysis. All data analysis was conducted on Empower software. Results: Totally, 18637 participants were enrolled in this study, of which 208 were migraineurs. The rest were set as control. There existed a statistically significant difference in mean age (P =0.0389), gender (P <0.0001), race (P <0.0001), data release cycle (P =0.048), drug usage, blood albumin (P <0.0001), blood total protein (P <0.0001), hemoglobin (P <0.0001), serum iron (P <0.0001) and serum urate (P <0.0001) between the two groups. According to logistic regression models, there existed no consistent linear relationship between serum urate and migraine before (model 1: odd ratio (OR) = 0.83, P= 0.0004) or after adjusting for confounders (model 2: OR= 0.96, P= 0.5198; model 3: OR= 0.84, P= 0.0184). However, smooth curve ﬁttings found an exponential curve relationship between serum urate and migraine. Furthermore, when serum urate was more than 7.8 mg/dL, higher serum urate was correlated with higher migraine occurrence (model 1: OR= 1.54, P= 0.0022; model 2: OR= 1.51, P= 0.0050; model 3: OR= 1.77, P= 0.0348). And 8 out of the 208 migraineurs had a serum urate higher than 7.8mg/dL. Conclusions: In conclusion, there existed an exponential curve relationship between serum urate and migraine, with an infliction point of 7.8 mg/dL. When serum urate was more than 7.8 mg/dL, elevated serum urate was correlated with higher migraine occurrence.